Ocean and climate synergies : from ocean warming to rising sea levels - UN.ESCAP; Castillo, Manuel; Mathew, Dayana; Karmel, Moehammad Ediyan Raza (United Nations, 2022)
This working paper compiles major impacts of climate change on the ocean, focusing on ocean warming, rising sea levels and ocean acidification. It compiles the reports and projections about ocean and climate in the Asia-Pacific region, emphasizing on extreme weather events, heatwave, coral bleaching, fish migration, degradation of the marine ecosystems, and biodiversity. It also provides sea-level calculations based on satellite data and statistical tools with Asia and Pacific regional examples.